The Role Of Animal Police In The Process Of Disclosing A Crime (Study At The K-9 Unit Of Bali Regional Police) - I Kadek Merta Arya Wiguna; Ni Ketut Wiratny; I Made Mulyawan Subawa (Al-Makki Publisher, 2024)
The K-9 Unit of the Bali Regional Police is an elite unit specializing in using sniffer dogs to assist in various police operations, ranging from apprehending criminals and detecting narcotics, to search and rescue (SAR) operations. The ability of sniffer dogs to detect narcotics and explosives is crucial in crime prevention and control efforts. In Bali, an international tourist destination, the threat of narcotics smuggling is very high. Specially trained sniffer dogs can quickly identify the presence of these illegal substances in various locations, such as airports, seaports, and entertainment venues. This study aims to identify and analyze the role of the K-9 Unit of the Bali Regional Police in the process of crime disclosure. Through a qualitative approach with a case study method, data were collected through interviews, observations, and literature studies. Through methods of observation, interviews, and literature study, this research is expected to provide a comprehensive and in-depth overview of the role of the K-9 Unit of the Bali Regional Police. The K-9 Unit of the Bali Regional Police has a significant contribution to disclosing crimes by providing technical assistance using sniffer dogs, which have proven effective in crime scene investigation and have a direct impact on solving criminal cases. Factors affecting the effectiveness of this unit include public demand, environmental conditions, and the availability of human and animal resources. To optimize its role, it is necessary to enhance training, facilities, coordination with related parties, and regular evaluation of the unit's performance.